New sources of papain: SEM and SDS‐PAGE analysis to determine the natural tenderizer from papaya latex and senesced leaves - Aprilia Indra Kartika; Hapsari Sulistya Kusuma; Sri Darmawati (Universitas Gadjah Mada, 2022)
This study aims to determine the effectiveness of papaya‐fruit latex and yellow‐senesced leaves as a natural and organic tenderizer. The fruit and leaves of the plant were ground to powder, while 0 g, 10 g, 15 g and 20 g variations were used to cover 50 g of meat for 4 h. Subsequently, the Bradford and Kjeldahl methods were used to determine the protein content, while the protein profile was analyzed using SDS‐PAGE and confirmed using a Scanning Electron Microscope (SEM). The results showed that the protein concentration in mutton after fruit latex treatment was 41%, which was higher than the concentration of beef at 29.86%. Furthermore, the beef lost protein bands and its molecular weight fell from 225 kDa to 86 KDa, while the mutton experienced a reduction from 100 kDa to 65 kDa, which was significantly smaller than for raw meat. A single protein band was also observed at 21.6 kDa in the sample, indicating the presence of papain enzyme protein. Meanwhile, the SEM results showed that collagen and myofibril in the muscles were damaged in the treated meats. Based on these results, treatment with papaya fruit latex and yellow papaya leaves increases the tenderness of meat.